A new efficient nonlinear programming based method for branch overload elimination - Abrantes,Heder D. (2003)
A simple and efficient method for eliminating branch overloads in power systems is presented in this paper. The overloads are eliminated by corrective control actions, which are defined through the use of an efficient and accurate nonlinear programming method. Generation rescheduling (GR) and load shedding (LS) are the main controls used. The idea of adaptative local optimization (ALO) is introduced. The computation of appropriate GR using ALO becomes a very efficient process. LS is used as a last resort, when further GR is no longer possible. Heuristics are added in order to speed up the computation process and to take into account some practical aspects of power systems operation into it. A special procedure is carried out in case of critical situations, where emergency control actions are defined. The method's general idea is to keep the new secure operating point as close as possible to the original one, while minimizing the amount of LS. The method can be a helpful tool for operation planning studies, security analysis and reliability evaluation of power systems. Simulations have been carried out for small test to large real life systems in order to show the efectiveness of the proposed method.